2016
DOI: 10.1097/md.0000000000004065
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of combined preoperative lactate dehydrogenase and alkaline phosphatase levels in patients with resectable pancreatic ductal adenocarcinoma

Abstract: Serum enzymes, including lactate dehydrogenase (LDH) and alkaline phosphatase (ALP), have recently been reported to play important roles in tumor growth. Increases in LDH and ALP have been confirmed to predict poor prognosis in patients with various cancers. However, their prognostic value in pancreatic cancer has not been well studied. Therefore, we reviewed the preoperative data on LDH and ALP in 185 pancreatic ductal adenocarcinoma (PDAC) patients who underwent surgery between July 2005 and December 2010 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 35 publications
(39 reference statements)
3
27
0
1
Order By: Relevance
“…We found that high ALP levels independently predict poor prognosis in patients with unresectable advanced gastric cancer, indicating that such levels could be used to reflect clinical prognosis. These findings support previous studies that proposed ALP or LDH as prognostic markers in hepatocellular carcinoma, esophageal squamous cell carcinoma, nasopharyngeal carcinoma, and pancreatic carcinoma [7,8,[16][17][18][19]. This is the first study to demonstrate the relationship between ALP levels and prognosis in gastric cancer patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that high ALP levels independently predict poor prognosis in patients with unresectable advanced gastric cancer, indicating that such levels could be used to reflect clinical prognosis. These findings support previous studies that proposed ALP or LDH as prognostic markers in hepatocellular carcinoma, esophageal squamous cell carcinoma, nasopharyngeal carcinoma, and pancreatic carcinoma [7,8,[16][17][18][19]. This is the first study to demonstrate the relationship between ALP levels and prognosis in gastric cancer patients.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, some investigators reported that ALP and LDH appeared to be reliable parameters to predict prognosis for various malignancies such as pancreatic cancer or esophageal squamous cell carcinoma [7,8]. However, the influence of serum enzymes such as ALP and LDH has not been reported in gastric cancer patients with regard to prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Liver function test is a basic routine examination before surgery. Some of its components, including alanine aminotransferase (ALT), albumin (ALB), and alkaline phosphatase (ALP), have been shown to have prognostic values for postoperative pancreatic cancer patients . Therefore, to provide better prognostic indicators in patients with resectable pancreatic cancer, it is of interest to further dig into parameters of liver function test and identify potential preoperative biomarkers that can predict postoperative survival.…”
Section: Introductionmentioning
confidence: 99%
“…Hasnyálmirigyrákban (n = 185) a kiindulási LDH<240 U/l hosszabb egy-, három-és ötéves betegségmentes túléléssel korrelált (60%, 26,8%, 19,9% vs. 22,2%, 5,2%, 2,6%, p<0,001) [105].…”
Section: A Kiindulási Szérum-ldh éS a Rosszindulatú Daganatos Betegekunclassified